Feasibility of Systematic Respiratory-Gated Acquisition in Unselected Patients Referred for 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography - Robin, Philippe; Bourhis, David; Bernard, Brieuc; Abgral, Ronan; Querellou, Solène; Le Duc-Pennec, Alexandra; Le Roux, Pierre-Yves; Salaün, Pierre-Yves (Frontiers in Medicine, 2018)
Objective Respiratory motion in 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) induces blurred images, leading to errors in location and quantification for lung and abdominal lesions. Various methods have been developed to correct for these artifacts, and most of current PET/CT scanners are equipped with a respiratory gating system. However, they are not routinely performed because their use is time-consuming. The aim of this study is to assess the feasibility and quantitative impact of a systematic respiratory-gated acquisition in unselected patients referred for FDG PET/CT, without increasing acquisition time. Methods Patients referred for a FDG PET/CT examination to the nuclear medicine department of Brest University Hospital were consecutively enrolled, during a 3-month period. Cases presenting lung or liver uptakes were analyzed. Two sets of images were reconstructed from data recorded during a unique acquisition with a continuous table speed of 1 mm/s of the used Biograph mCT Flow PET/CT scanner: standard free-breathing images, and respiratory-gated images. Lesion location and quantitative parameters were recorded and compared. Results From October 1 2015 to December 31 2015, 847 patients were referred for FDG PET/CT, 741 underwent a respiratory-gated acquisition. Out of them, 213 (29%) had one or more lung or liver uptake but 82 (38%) had no usable respiratory-gated signal. Accordingly, 131 (62%) patients with 183 lung or liver uptakes were analyzed. Considering the 183 lesions, 140 and 43 were located in the lungs and the liver, respectively. The median (IQR) difference between respiratory-gated images and non-gated images was 18% (4−32) for SUVmax, increasing to 30% (14−57) in lower lobes for lung lesions, and −18% (−40 to −4) for MTV (p < 0.05). Technologists’ active personal dosimetry and mean total examinations duration were not statistically different between periods with and without respiratory gating. Conclusion This study showed that a systematic respiratory-gated acquisition without increasing acquisition time is feasible in a daily routine and results in a significant impact on PET quantification. However, clinical impact on patient management remains to be determined.